Global and regional burden of first-ever ischaemic and haemorrhagic stroke during 1990-2010: findings from the Global Burden of Disease Study 2010 - Rita V Krishnamurthi, PhD; Prof. Valery L Feigin, MD; Prof. Mohammad H Forouzanfar, MD; George A Mensah, MD; Myles Connor, MBBCh; Derrick A Bennett, PhD; Prof. Andrew E Moran, MD; Prof. Ralph L Sacco, MD; Laurie M Anderson, PhD; Thomas Truelsen, MD; Prof. Martin O'Donnell, PhD; Narayanaswamy Venketasubramanian, MBBS; et al. (Elsevier, 2013)
Background: The burden of ischaemic and haemorrhagic stroke varies between regions and over time. With differences in prognosis, prevalence of risk factors, and treatment strategies, knowledge of stroke pathological type is important for targeted region-specific health-care planning for stroke and could inform priorities for type-specific prevention strategies. We used data from the Global Burden of Diseases, Injuries, and Risk Factors Study 2010 (GBD 2010) to estimate the global and regional burden of first-ever ischaemic and haemorrhagic stroke during 1990-2010. Methods: We searched Medline, Embase, LILACS, Scopus, PubMed, Science Direct, Global Health Database, the WHO library, and regional databases from 1990 to 2012 to identify relevant studies published between 1990 and 2010. We applied the GBD 2010 analytical technique (DisMod-MR) to calculate regional and country-specific estimates for ischaemic and haemorrhagic stroke incidence, mortality, mortality-to-incidence ratio, and disability-adjusted life-years (DALYs) lost, by age group (aged <75 years, ≥75 years, and in total) and country income level (high-income and low-income and middle-income) for 1990, 2005, and 2010. Findings: We included 119 studies (58 from high-income countries and 61 from low-income and middle-income countries). Worldwide, the burden of ischaemic and haemorrhagic stroke increased significantly between 1990 and 2010 in terms of the absolute number of people with incident ischaemic and haemorrhagic stroke (37% and 47% increase, respectively), number of deaths (21% and 20% increase), and DALYs lost (18% and 14% increase). In the past two decades in high-income countries, incidence of ischaemic stroke reduced significantly by 13% (95% CI 6-18), mortality by 37% (19-39), DALYs lost by 34% (16-36), and mortality-to-incidence ratios by 21% (10-27). For haemorrhagic stroke, incidence reduced significantly by 19% (1-15), mortality by 38% (32-43), DALYs lost by 39% (32-44), and mortality-to-incidence ratios by 27% (19-35). By contrast, in low-income and middle-income countries, we noted a significant increase of 22% (5-30) in incidence of haemorrhagic stroke and a 6% (-7 to 18) non-significant increase in the incidence of ischaemic stroke. Mortality rates for ischaemic stroke fell by 14% (9-19), DALYs lost by 17% (-11 to 21%), and mortality-to-incidence ratios by 16% (-12 to 22). For haemorrhagic stroke in low-income and middle-income countries, mortality rates reduced by 23% (-18 to 25%), DALYs lost by 25% (-21 to 28), and mortality-to-incidence ratios by 36% (-34 to 28). Interpretation: Although age-standardised mortality rates for ischaemic and haemorrhagic stroke have decreased in the past two decades, the absolute number of people who have these stroke types annually, and the number with related deaths and DALYs lost, is increasing, with most of the burden in low-income and middle-income countries. Further study is needed in these countries to identify which subgroups of the population are at greatest risk and who could be targeted for preventive efforts. Funding: Bill & Melinda Gates Foundation.